2022
DOI: 10.1155/2022/8696084
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of MDT Collaborative Nursing Combined with Hierarchical Nursing Management Model on the Quality of Life and Comfort of Patients with Gallbladder Stones Combined with Acute Cholecystitis after Surgery

Abstract: Objective. To explore the effect of MDT (multidisciplinary team) collaborative nursing combined with hierarchical nursing management mode on the quality of life and comfort of patients with gallbladder stones combined with acute cholecystitis after surgery. Methods. A total of 120 patients with gallbladder stones and acute cholecystitis who were treated in our hospital from March 2019 to March 2021 were selected as prospective research objects. According to the order of care, they were divided into control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Through the optimization of various nursing processes, the time of pick-up and drop-off in the operating room and the preparation time could be significantly shortened, improving the work efficiency. This would ensure the patient can be more quickly accepted to the treatment, Am J Transl Res 2024;16(2):506-514 and to a certain extent, can enhance the effectiveness of clinical treatment [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Through the optimization of various nursing processes, the time of pick-up and drop-off in the operating room and the preparation time could be significantly shortened, improving the work efficiency. This would ensure the patient can be more quickly accepted to the treatment, Am J Transl Res 2024;16(2):506-514 and to a certain extent, can enhance the effectiveness of clinical treatment [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…This is essential to cater to the diverse surgical requirements of patients, enhance the overall quality of medical collaboration, and boost patient satisfaction. Currently, the prevailing MDT diagnosis and treatment method in China involves a team of doctors in the clinical department and an inhouse team of nurses, as described in multiple studies [5][6][7] . Only a few operating room nurses are involved in the preoperative discussions held by the multidisciplinary clinical diagnosis and treatment team.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%